2017
DOI: 10.1007/s00167-017-4545-3
|View full text |Cite
|
Sign up to set email alerts
|

Disc degeneration on MRI is more prevalent in young elite skiers compared to controls

Abstract: PurposeEvidence-based facts regarding spine abnormalities and back pain are needed in order to develop rehabilitation programs and prevent spine injuries in young skiers. The aim therefore is to identify MRI changes in the thoraco-lumbar spine and the lifetime prevalence of back pain, as well as the association between them, in young skiers compared to non-athletes.MethodsSeventy-five young elite alpine and mogul skiers, age range 16–20 years, were compared with 27 non-athletic controls. All subjects underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…These factors are known to be related to high spinal disk loading, 28 as well as the high peak loads encountered on the slope due to snow hardness and the ski discipline itself 29,30 . Therefore, repeated impacts on immature spine may have led to chronic endplate lesions 15 . Two factors may have attenuated the increase in back lesions across the last year studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors are known to be related to high spinal disk loading, 28 as well as the high peak loads encountered on the slope due to snow hardness and the ski discipline itself 29,30 . Therefore, repeated impacts on immature spine may have led to chronic endplate lesions 15 . Two factors may have attenuated the increase in back lesions across the last year studied.…”
Section: Discussionmentioning
confidence: 99%
“…The age distribution of participants was relatively narrow and specific, and the generalizability to other athletes’ levels cannot be ascertained. Indeed, the rate of back lesions may currently be lower in more experienced skiers 15 (World Cup: 43% (15/35) vs 64% (18/28) in Europa Cup, unpublished data over season 2016/2017). Due to low sample size, the increase in spine lesions was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies demonstrated the higher incidence of Schmorl's node in athletes compared with nonathletes. 1, [67][68][69] For example, Witwit et al reported an incidence of 46% in skiers compared with 0% in a control group, 68 and Swärd et al demonstrated a 71% incidence in gymnasts, compared with 44% in nonathletes. 1 Axial loading is thought to play a role in the formation of Schmorl's node, accounting for their observation in sports such as diving, weightlifting, and even ice hockey (axial loading is thought to be produced in high-speed skating and forceful midair tackles).…”
Section: Anterior Limbus Vertebramentioning
confidence: 99%
“…Several studies have shown associations between competitive sports activities and degenerative pathology of the spine [1][2][3][4][5][6][7][8][9][10][11][12][13] . Olympic sports are no exception since Olympic athletes spend a considerable amount of time training and competing relying on strength, speed, force, bending, and twisting in their sport.…”
Section: Introductionmentioning
confidence: 99%